Hero or scholar : the ideal Singaporean Chinese man in dating relationships - Fong, Florence (2017)
This paper examines contradictions faced by young Singaporean Chinese men in dating relationships today, in negotiations of their masculinities. With reference to ‘Chinese masculinity’ (Kam 2002), I explore these men’s notions of ‘masculinity’. Through interviews conducted, I identify attributes that they associate with being ‘masculine’, as well as the frames of references from which they attain these ideals. I conclude that these men hold 3 ‘back-stage’ (Goffman 1959) gender ideologies: traditional, egalitarian, and transitional. With their ‘front-stage’ performances different from these ‘back-stage’ ones, most respondents experience discrepancy strain. While this paper confirms current literature on reflexivity of masculinities with femininities, one aspect that have resulted in these men’s different ‘front-stage’ and ‘back-stage’ behaviors, I also identify economic realities as another cause. Lastly, I highlight gender strategies employed by these men to alleviate these tensions. This way, they can preserve manhood ideals, while managing pressures from their partners and economic realities.